Komparasi Rasio Profitabilitas: PT. Telkom Indonesia Sebelum dan Selama Pandemi Covid-19 - Fitriyani, Diah; Nisa', Zulfatin; Zamzami, Mohammad Dimyati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The key in assessing the success of a country is to look at the conditions in maintaining its economy, especially during the coronavirus disease (covid-19) pandemic which makes the world economy weaken. One of the negative impacts is that many large companies go bankrupt, requiring companies to lay off their employees. On the other hand, there are also companies that are able to survive and even experience an increase during the COVID-19 pandemic. Some telecommunication companies were able to survive during the pandemic due to the increasing demand for internet services, one of which is PT. Telkom Indonesia. In general, to determine the success of PT. Telkom Indonesia can see this from the analysis of the performance of its financial statements, one of which uses the profitability ratio. Profitability ratio is a ratio that measures the company's strength to earn profits. The purpose of this study was to compare the profitability ratios of PT. Telkom Indonesia (Persero) Tbk before and during the covid-19 pandemic. The type of research used is descriptive quantitative research by utilizing the financial report data of PT. Telkom Indonesia. The analysis was carried out by comparing the profitability ratios of PT. Telkom Indonesia before and during the covid-19 pandemic. The product of the research shows that before and during the onset of COVID-19 the company was still able to survive and make a profit on asset management, equity, and sales.